Design and Analysis of Lifting Lugs and Supporting Platform for CFETR 1/8 Vacuum Vessel Mock-Up. (2nd January 2020) - Lu, Kun; Qin, Shijun; Wang, Qingfeng; Liu, Peng; Mao, Xin; Zhang, Yang; Xu, Zhuang; Liu, Zhihong; Liu, Chen; Wei, Jing; Shen, Guang; Liu, Sumei; et al.
Abstract: The China Fusion Engineering Test Reactor (CFETR) is a new superconducting magnet tokamak. The vacuum vessel (VV) is one of the core components of the CFETR device, and it will provide a high-vacuum environment for the plasma, improve radiation shielding and plasma stability, and provide support for in-vessel components. The 1/8 VV sector mock-up has been designed and manufactured in the Chinese Academy of Sciences, Institute of Plasma Physics (ASIPP) from a few years ago to verify the design and key technologies to be used in the future. The production and assembly of the 1/8 VV sector are not in the same place, so lifting lugs and a support platform were designed for lifting and supporting the 1/8 VV sector mock-up. The detailed design of the 1/8 VV sector mock-up lifting lugs and support platform are described. There are two design options for the lifting lugs—removable and nonremovable—and there are also two design options—the integral and the separated—for the supporting platform. At the same time finite element analysis and assessment of the lifting lugs and supporting platform were done. The maximum stress does not exceed the allowable stress of the material, in consequence both of the two design options are practicable, respectively. All the design and analysis results will provide technical support for the assembly of the 1/8 VV sector in the future.